MEMBANGUN PARTISIPASI MASYARAKAT MISKIN DALAM PENGUATAN DEMOKRASI DI PROVINSI DAERAH KHUSUS IBUKOTA JAKARTA - Rahmatullah Rahmatullah (Jurnal Ilmiah Mimbar Demokrasi, 2014)
The existence of a democratic system is strongly influenced by the participation of all parties, including the poor. So far, the poor always associated as apathetic and irrational in politics. and consider any political change will not be much change their fate. However, in the case of DKI Jakarta showed that they are a group of rational, transparent, and participatory enough in politics, though not to the extent that satisfactory. Their knowledge of politics obtained directly from a variety of media and existing facilities. Because it is necessary for the political strengthening of the urban poor, in the form of strengthening the political culture of the participants, which puts them have a real orientation of the systems, structures and processes of political and administrative .. That way they can be involved in a variety of policies oriented towards the improvement of people's lives rate. The phenomenon of the political life of the urban poor is not merely seen from political participation in the form of political activity, but also a social activity